PENGARUH CAREER, KNOWLEDGE MANAGEMENT DAN LEADERSHIP TERHADAP KEPUASAN KERJA KARYAWAN CHEVRON GEOTHERMAL DI INDONESIA - Agus Prabowo (Universitas Mercu Buana, 2014)
Abstract. Career management is inadequate, the implementation of knowledgemanagement systems that are less disciplined in supporting work processes andleadership ability, a factor predictable problems that can hamper job satisfactionof employees of the company in the pursuit of the competence to be a globalworkforce of talented high. This study aims at examine and analyze the influenceof Career, Knowledge Management and Leadership on Employee Job Satisfactionof Chevron Geothermal in Indonesia. This research design used quantitativemethod. The population of this research, all staff and associcate staff employeesof Chevron Geothermal in Indonesia as many as 525 employees. The samplingtechnique use proportional random sampling. The number of sample is 84employees uses Slovin Method. The method of analysis used in the research ismultiple linear regression analysis method with SPSS version 22.0. The resultsshowed that Career, Knowledge Management and Leadership simultaneously arehaving influence to employee job satisfaction of Chevron Geothermal inIndonesia. Partially Career has a positive effect on employee job satisfaction. Aswell as Knowledge Management and Leadership have a positive effect onemployee job satisfaction. Career and Leadership are biggest variable ininfluencing the employee job satisfaction.Keywords: Career, Knowledge Management, Leadership, Employee JobSatisfaction.